Второй раз в первый класс - Трауб Маша (Проза Маши Трауб, 2019)
Экземпляры: аб (20201008) / Инвентарный номер: 55968 / Цена: 99.00 / Сис.шифр: Р2 / Авт.знак: Т 65 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6